Answer:
-12
Step-by-step explanation:
plug in -1 into the equation which is going to be (4*-1)3
you multiply what is in the parenthesis first and after is going to be (-4)3
lastly your going to multiply -4*3 and it is going to equal to -12.
Answer:
4096
Step-by-step explanation:
4x4x4x4x4x4=4^6
Group them to multiply to make it easier:
4x4=16
4x4=16
4x4=16
16x16x16=4096
honestly just plug it into a calculator
SAS since ∠RNM is congruent ∠PNQ by vertical angles which will give you the angle you need for SAS.
Answer:
6 students
Step-by-step explanation:
6 times 1.5 equals 9
We know that
surface area of the square pyramid=area of the base+4*[area of lateral triangle]
area of the base=b²----> area of square
b=6 ft
area of square=6*6---> 36 ft²
area of lateral triangle=b*h/2
b=6 ft
h=9 ft
area of lateral triangle=6*9/2---> 27 ft²
surface area of the square pyramid=36+4*27----> 144 ft²
the answer is
144 ft²